Atypical Presentation of Visceral Leishmaniasis in a HIV-positive Patient from a Nonendemic Area - Vyas, Dhara H (Medknow Publications & Media Pvt Ltd, 2011)
Visceral leishmaniasis (VL), though widely prevalent in India, is not seen in the Rajasthan where the dry, hot and arid climatic conditions create a hostile environment for the growth of the parasite or its vector, the sandfly. We present a case of VL in a patient co-infected with HIV from this region. A 34-year-old known case of a HIV-positive patient presented to the skin department of our hospital with multiple, nontender, erythematous, papulonodular lesions all over the body for 6 months with history of weight loss and low-grade fever. Important examination findings were pallor, inguinal lymphadenopathy and hepatosplenomegaly. Laboratory findings included anemia, leucopenia, hypergammaglobulinemia and altered leucocytes to erythrocyte ratio. Buffy coat examination and bone marrow aspirates showed the presence of leishman bodies inside monocytes and macrophages respectively as well as extracellularly also. The patient was treated with amphotericin B intravenously and responded well to the treatment.